Advanced control of multi-terminal DC/DC converter - Liu, Qingxiang (2019)
Three port active bridge (TAB) converter is an effective alternative to the conventional dual active bridge (DAB) for hybrid energy storage system (HESS) in microgrids and vehicular power systems. Nonetheless, most of the existing modulation strategies that allow soft-switching of TAB are designed for fuel cell applications, where two ports of TAB only deliver unidirectional power. Moreover, in these modulation approaches, soft-switching is usually achieved only when the terminal voltage of ultracapacitor (UC) varies in a very small range. This is undesirable for the full exploitation of UC, especially when it is utilized as a complement of batteries. In order to explore the applicability of modulation strategy for wide range voltage fluctuation or wide range power fluctuation, this thesis firstly studies the voltage and power range of the modulation strategy we proposed in the early research stage of this project. For reactive power eliminating purpose, two modulation strategies (variant 3 and its extension) are studied in this thesis. It is found that good output results can be obtained when the two modulation strategies are combined. Simulation results are presented to verify the efficacy of the proposed modulation strategy.